Implementasi Kebijakan Pendidikan Kesetaraan Di Dinas Pendidikan Kabupaten Banjarnegara (Studi Kasus: Program Nganter Anak Paud Dapat Lulus Ijazah SMA "Ternak Panda Lima") - Sari, Maunatul Mazida; Manar, Dzunuwanus Ghulam; -, Supratiwi - (Journal of Politic and Government Studies, 2024)
This study analyzes the implementation of the education equality policy in Banjarnegara Regency through the "Ternak Panda Lima" program, which aims to address high dropout rates and improve the average years of schooling (RLS) and the Human Development Index (HDI) in the region. Using Riant Nugroho's policy implementation theory, the research evaluates the program based on five aspects: appropriate policy, implementation, target, environment, and process. Data were collected through qualitative methods, including interviews, observations, and document studies. The findings reveal several challenges such as unclear standards and targets, limited human resources, inadequate facilities, and diverse socioeconomic conditions. However, successes include increased community participation and stakeholder collaboration. The results indicate that policy alignment with national goals is present but lacks clarity, affecting consistency. Implementation efforts are notable but hindered by resource limitations. The program targets the correct demographic but faces barriers in reaching them consistently. Socio-economic conditions significantly impact the program's success, with better outcomes in more advantaged areas. Effective stakeholder coordination exists but is limited by bureaucratic inefficiencies. Recommendations for improving the program's effectiveness include enhancing human resources, providing adequate facilities, and adjusting policies to local socio-economic conditions. The study concludes that the success of the "Ternak Panda Lima" program is influenced by the competency of policy implementers, stakeholder collaboration, and policy understanding